1998
DOI: 10.1007/s002130050533
|View full text |Cite
|
Sign up to set email alerts
|

The α -2a noradrenergic agonist, guanfacine, improves delayed response performance in young adult rhesus monkeys

Abstract: In aged monkeys with naturally occurring catecholamine depletion, alpha-2 adrenergic agonists such as guanfacine have repeatedly been shown to improve dorsolateral prefrontal cortical function, as assessed by the spatial delayed response task. Both low (0.0001-0.001 mg/kg) and high (0.5 mg/kg) but not intermediate (0.01-0.05 mg/kg) doses of guanfacine improve spatial working memory performance in aged animals. However, it is not known whether guanfacine would similarly improve performance in young animals. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
73
1
3

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 21 publications
5
73
1
3
Order By: Relevance
“…It is well documented that a 2 -, especially a 2A -adrenoceptors (ARs) in the PFC are involved in regulating working memory function (Arnsten et al, 1988;Arnsten and Goldman-Rakic, 1985;Arnsten and Li, 2005;Franowicz and Arnsten, 1998;Franowicz et al, 2002;Li and Mei, 1994;Mao et al, 1999). a 2 -AR agonists such as clonidine and guanfacine administered systemically or locally into the PFC improve working memory performance in rats and monkeys (Arnsten et al, 1988;Arnsten and Goldman-Rakic, 1985;Franowicz and Arnsten, 1998;Mao et al, 1999;Tanila et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is well documented that a 2 -, especially a 2A -adrenoceptors (ARs) in the PFC are involved in regulating working memory function (Arnsten et al, 1988;Arnsten and Goldman-Rakic, 1985;Arnsten and Li, 2005;Franowicz and Arnsten, 1998;Franowicz et al, 2002;Li and Mei, 1994;Mao et al, 1999). a 2 -AR agonists such as clonidine and guanfacine administered systemically or locally into the PFC improve working memory performance in rats and monkeys (Arnsten et al, 1988;Arnsten and Goldman-Rakic, 1985;Franowicz and Arnsten, 1998;Mao et al, 1999;Tanila et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…a 2 -AR agonists such as clonidine and guanfacine administered systemically or locally into the PFC improve working memory performance in rats and monkeys (Arnsten et al, 1988;Arnsten and Goldman-Rakic, 1985;Franowicz and Arnsten, 1998;Mao et al, 1999;Tanila et al, 1996). It has been shown that the beneficial effect of clonidine or guanfacine on working memory performance is mediated by a 2A -ARs (Arnsten et al, 1988;Arnsten and Li, 2005;Franowicz et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The release of low to moderate levels of NE activates a-2A adrenoceptors and improves PFC functions, such as working memory performance and attention (Arnsten and Goldman-Rakic 1985;Arnsten et al 1988;Franowicz and Arnsten 1998;Li et al 1999;Franowicz et al 2002;Wang et al 2007). By contrast, higher levels of NE, as well as stress, activate a-1 adrenoceptors and impair PFC functions (Arnsten and Jentsch 1997;Birnbaum et al 1999;Mao et al 1999;Marzo et al 2010).…”
mentioning
confidence: 99%
“…The a-2A agonist clonidine has been used widely in the treatment of ADHD children, 27 suggesting a potential role for the receptor in symptom expression. More definitive evidence emerges from recent work showing that the selective a-2A agonist guanfacine improves function on tasks reliant on prefrontal cortical functions in monkeys 11,28 and in humans, 26 but does not affect behavior when the prefrontal cortex is not challenged. 11 Thus, pharmacologic investigations point to an important role for the NE system, especially the a-2A receptor, in the cognitive operations of the prefrontal cortex that are suspected of involvement in ADHD.…”
mentioning
confidence: 99%